DAYA DUKUNG LAHAN DALAM PERENCANAAN TATA RUANG WILAYAH (STUDI KASUS KABUPATEN BLITAR, JAWA TIMUR) - Iman Sadesmesli; Dwi Putro Tejo Baskoro; Andrea Emma Pravitasari (Diponegoro University, 2017)
Land carrying capacity is important to be considered in spatial planning. This study was aimed to evaluate the land carrying capacity of the spatial planning of Blitar Regency using land capability evaluation. Evaluation was done by assesing the conformity between the actual land utilization and land allocation of the Official spatial planning of Blitar Regency toward the land capability. The class of land capability was evaluated for each land unit, which was combined from landforms and soil survey from the previuos research. The actual land use analysis was done by updating land use maps that have been provided by the SPOT-6 images acquired in 2015. The result showed that land capablity in Blitar Regency was consist of class II, III, IV, VI, VII and class VIII. The area with land capablity class of II to IV which supported agricultural cultivation were only 39.0% of total area, meanwhile 61.0% of total area should not be used for agricultural cultivation (class VI to VIII). The actual land carrying capacity based on the conformity between the actual land use and land capability were only 69.662 ha (43,8%), while the land carrying capacity of planning aspect based on the conformity between the official spatial planning and land capability was reached 79.498 ha (50,0%).